TO EVALUATE THE EFFECT OF MORUS ALBA LEAVES EXTRACT ON SLEEP AND ANXIETY IN RAT MODELS - RAYAM, SRIHARSHA; BL, KUDAGI; JONNALAGADDA, RAMYA; NALLABOTHULA, RAVEENDRA KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to study the effect of Morus alba leaves extract (MAE) on sleep by phenobarbitone-induced sleeping time and the antianxiety effect by elevated plus maze apparatus model in rats. Methods: In this study, the effect of MAE on sleep was evaluated by the phenobarbitone-induced sleeping time of rats. The onset and the duration of sleep were recorded in minutes. The antianxiety effect was evaluated by the elevated plus maze apparatus model in rats. During 5 min test period, the number of entries into the open arm and closed arm and time spent in the open arm and closed arm were recorded in seconds. Results: MAE at the dose 200 and 400 mg/kg, highly significantly (p<0.001) decreased the onset of phenobarbitone-induced sleeping time. The duration of sleeping time was increased significantly (p<0.01) for 200 mg/kg and highly significantly (p<0.001) for 400 mg/kg as compared to the control group. M. alba has significant antianxiety activity in comparison with control in a dose-dependent manner. M. alba in a dose of 200 mg showed significant (p<0.01) and 400 mg/kg treated groups showed highly significant (p<0.001) anxiolytic activity by increasing the mean time spent in open arms as compared to control but less significant with standard (diazepam). Conclusion: Results indicate that the MAE has a significant dose-dependent effect on phenobarbitone- induced sleeping time and antianxiety effect in the elevated plus maze test.